2021
DOI: 10.1186/s12889-021-10432-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of parents’ knowledge and awareness regarding paracetamol use in children: a cross-sectional study from Palestine

Abstract: Background Paracetamol, also known as acetaminophen, is one of the most common antipyretic and analgesic over-the-counter (OTC) medicines administered to children due to its efficacy, safety, and availability in many pharmaceutical forms, including suppositories, syrup, and drops. Parents frequently administer the wrong dose of paracetamol by mistake for their children, as reported by many previous studies. We aimed in this study to assess parents’ knowledge, attitudes, and practice regarding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 41 publications
4
29
0
2
Order By: Relevance
“…This study revealed that the majority of parents used paracetamol for fever which is consistent with a few studies (Daifallah et al, 2021;Lundgren et al, 2017). Paracetamol is generally not required for the treatment of mild fever under a body temperature of less than 38.5°C (Chong et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that the majority of parents used paracetamol for fever which is consistent with a few studies (Daifallah et al, 2021;Lundgren et al, 2017). Paracetamol is generally not required for the treatment of mild fever under a body temperature of less than 38.5°C (Chong et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The indiscriminate use of medication to control pain increases unintentional poisoning, with simultaneous administration of two or more formulations with paracetamol ( Larson et al, 2005 ). Poor knowledge of consumers about adverse events related to the drug may also increase risks and unintentional poisoning ( Daifallah et al, 2021 ). In addition to the consumption of different compounds with acetaminophen, easy access without a prescription, and self-medication, the concomitant use with alcohol further damages the liver function and increases the risk of unintentional poisoning ( Kane et al, 2012 ; Kjartansdottir et al, 2012 ; Hawton et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parasetamol adalah obat yang digunakan sebagai analgesik (pereda nyeri) dan antipiretik (penurun panas/demam) yang bisa diperoleh tanpa resep dokter [4][5][6] . Parasetamol drops merupakan suatu sediaan yang biasanya ditujukan kepada anakanak 5 . Mulai dari umur 0 bulan sampai sampai 3 tahun.…”
Section: Pendahuluanunclassified
“…Metode yang dilakukan adalah mencampur parasetamol drops dengan minuman teh manis dan disimpan pada kondisi penyimpanan suhu ruang (≤ 30 ⁰C) dan suhu dingin (2-8 ⁰C). Pada interval waktu 0, 5,10, 15,20,30, 45, 60, 120, 180 dan 1440 menit dilakukan pengamatan organoleptik dan penetapan kadar parasetamol menggunakan Spektrofotometri UV-Vis. Hasil pengujian organoleptik menunjukkan campuran stabil berbentuk cair berwarna merah dengan aroma khas parasetamol dan sedikit aroma teh selama 24 jam penyimpanan pada suhu dingin.…”
unclassified